Late Cenozoic tephrostratigraphy offshore the southern Central American Volcanic Arc: 1. Tephra ages and provenance. (21st November 2016) - Schindlbeck, J. C.; Kutterolf, S.; Freundt, A.; Alvarado, G. E.; Wang, K.‐L.; Straub, S. M.; Hemming, S. R.; Frische, M.; Woodhead, J. D.
Abstract: We studied the tephra inventory of 18 deep‐sea drill sites from six DSDP/ODP legs (Legs 84, 138, 170, 202, 205, and 206) and two IODP legs (Legs 334 and 344) offshore the southern Central American Volcanic Arc (CAVA). Eight drill sites are located on the incoming Cocos plate and 10 drill sites on the continental slope of the Caribbean plate. In total, we examined ∼840 ash‐bearing horizons and identified ∼650 of these as primary ash beds of which 430 originated from the CAVA. Correlations of ash beds were established between marine cores and with terrestrial tephra deposits, using major and trace element glass compositions with respect to relative stratigraphic order. As a prerequisite for marine‐terrestrial correlations, we present a new geochemical data set for significant Neogene and Quaternary Costa Rican tephras. Moreover, new Ar/Ar ages for marine tephras have been determined and marine ash beds are also dated using the pelagic sedimentation rates. The resulting correlations and provenance analyses build a tephrochronostratigraphic framework for Costa Rica and Nicaragua that covers the last <15 Myr. We define 39 correlations of marine ash beds to specific tephra formations in Costa Rica and Nicaragua; from the 4.15 Ma Lower Sandillal Ignimbrite to the 3.5 ka Rincón de la Vieja Tephra from Costa Rica, as well as another 32 widely distributed tephra layers for which their specific region of origin along Costa Rica and Nicaragua can be constrained. Key Points: Explosive volcanism from Costa Rica and Nicaragua Provenance, tephrostratigraphy, and tephrochronology IODP/ODP/DSDP drill sites